2010
DOI: 10.2478/v10152-010-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening in Kosovo: women's knowledge and behaviours

Abstract: Background: Breast cancer is the most common cancer affecting women all over the world. It is estimated to account for around 25% of all malignancies in women, and its incidence shows a continuously increasing trend in many countries 52,7 % `ensk, ki `ivijo zunaj mest (p<0,01). Poznale so naslednje presejalne metode: klini~no preiskavo dojk (24,8 %), samopregledovanje dojk (12,6 %), mamografijo in ultrazvo~no preiskavo (5,0 %)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…However, these studies carried out in Qom, Iran showed only 61.9% of respondents had a good level of knowledge [23] . About 97% the respondents showed that the method of screening of breast cancer by BSE in this study and this specific finding is higher than previous findings like 12.6% [24], 19% [25], 74.2% [17], 81.4% [26] respectively.…”
Section: Knowledge About Methods Of Screening For Breast Cancercontrasting
confidence: 75%
“…However, these studies carried out in Qom, Iran showed only 61.9% of respondents had a good level of knowledge [23] . About 97% the respondents showed that the method of screening of breast cancer by BSE in this study and this specific finding is higher than previous findings like 12.6% [24], 19% [25], 74.2% [17], 81.4% [26] respectively.…”
Section: Knowledge About Methods Of Screening For Breast Cancercontrasting
confidence: 75%